“Social Impact of Pandemic disease (COVID-19) in General Population - Stephina Fernandes1 , Sharadha Ramesh2 , Merlin Suji1, Poonam Yadav1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Abstract:The COVID-19 pandemic has swept the entire world off its feet by its deadly outcomes andIndia is no exception to it. The pandemic has affected our country in many different terms that has causeddifferent issues for the general public and rendering many jobless. There were many problems cause likeeconomic loss, loss of life, business, jobs etc2. Considering this current situation, this research is be basedon highlighting the social impact of the pandemic disease on the general population. Methodology: ANon-Experimental Descriptive Research Approach “Quantitative research which involves the collectionand collation of numerical information under considerable control.” The study was conducted among thegeneral population of Pune City. The selection of sample was based on easy geographical accessibility,willingness of the samples and availability of samples. The sample size for study was 100, selected by usingNon Probability Convenience Sampling Technique from various residents living in Pune City who metthe inclusion criteria. A structured modified questionnaire was developed based on the research problem,to get the information from the samples. Objective: 1) To assess the effect of lockdown on social life ingeneral population in selected area of Pune city. 2) To assess the obstacles faced by general public during theCovid-19 pandemic. 3) To associate the demographic variables with the lockdown effect and obstacles inselected areas of Pune City. Result: The analysis shows that the family relations of 28.6% population wereseverely affected by the pandemic situation and 69.84% of population were less affected by it. The socialrelations and recreation of 76.19% population were severely affected by the pandemic situation and 15.9%of population were less affected by it. The 74.6% population were severely affected psychologically due tothe pandemic situation and 14% of population were less affected psychologically. Also 79.37% populationwere faced severely difficulties in getting the basic necessities during the pandemic situation while 12.7%of population faced less problems in procuring the basic necessities. Also 36.51% population faced severobstacles related to work while 52.4% of population faced less obstacles by it. Since all the p-valuescorresponding to gender is less (less than 0.05). Hence gender is to have significant association with thelockdown effect and obstacles. Conclusion: This research concludes that COVID-19 has had a great effecton social relations, psychological aspect